substituteGiven:-
![(0,0),(-3,0)(-1,3)](https://img.qammunity.org/2023/formulas/mathematics/college/44a12nr6e68pb0ufeiv2bt722rmcsxno0o.png)
To find the quadratic equation.
So now we use the formula,
![y=ax^2+bx+c](https://img.qammunity.org/2023/formulas/mathematics/high-school/g7mvpjunjwe6qob7ddy7l4f0glbtdi9gci.png)
So now we subtitute the points and find the value of a,b,c. So we get,
![\begin{gathered} 0=a(0)+b(0)+c \\ c=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/uwnhsehnpyet2ra79laykbjr84ucf8dy3b.png)
Also,
![\begin{gathered} 0=a(-3)^2+b(-3)+c \\ 0=9a-3b \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/bn27g6gblzw0dh3l951weynsys0qigqy85.png)
Also,
![\begin{gathered} 3=a(-1)^2+b(-1)+0 \\ 3=a-b \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/hzux4ff1i0cn3a8mm3tev922hs5x909q7b.png)
So now we simplify both equation. so we get,
![\begin{gathered} 9a-3b=0 \\ 3a-3b=9 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/z8lncfl4u39siocv1l48rrj2gtlhqlebi9.png)
Now we add both the equations. we get,
![\begin{gathered} 6a=-9 \\ a=-(3)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1oomu95p342qf2f2otqgq0d3cuh3wr50kl.png)
Now we find the value of b, so we get,
![\begin{gathered} a-b=3 \\ -(3)/(2)-b=3 \\ -b=3+(3)/(2) \\ -b=(9)/(2) \\ b=-(9)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/uoob9yo32jhwn04nkd6fi5nesrn3ujdv5h.png)
So the required values are,
![y=-(3)/(2)x^2-(9)/(2)x+0](https://img.qammunity.org/2023/formulas/mathematics/college/c4wtqh85fgjqtmqjsm8x75al1ateterp1i.png)